Butyrate production in the acetogen Eubacterium limosum is dependent on the carbon and energy source. Issue 6 (25th February 2021) - Litty, Dennis; Müller, Volker
Summary: Eubacterium limosum KIST612 is one of the few acetogenic bacteria that has the genes encoding for butyrate synthesis from acetyl‐CoA, and indeed, E. limosum KIST612 is known to produce butyrate from CO but not from H2 + CO2 . Butyrate production from CO was only seen in bioreactors with cell recycling or in batch cultures with addition of acetate. Here, we present detailed study on growth of E. limosum KIST612 on different carbon and energy sources with the goal, to find other substrates that lead to butyrate formation. Batch fermentations in serum bottles revealed that acetate was the major product under all conditions investigated. Butyrate formation from the C1 compounds carbon dioxide and hydrogen, carbon monoxide or formate was not observed. However, growth on glucose led to butyrate formation, but only in the stationary growth phase. A maximum of 4.3 mM butyrate was observed, corresponding to a butyrate:glucose ratio of 0.21:1 and a butyrate:acetate ratio of 0.14:1. Interestingly, growth on the C1 substrate methanol also led to butyrate formation in the stationary growth phase with a butyrate:methanol ratio of 0.17:1 and a butyrate:acetate ratio of 0.33:1. Since methanol can be produced chemically from carbon dioxide, this offers the possibility for a combined chemical‐biochemical production of butyrate from H2 + CO2 using this acetogenic biocatalyst. With the advent of genetic methods in acetogens, butanol production from methanol maybe possible as well. Abstract : In this study, we have investigated the growth of and product formation by the acetogen Eubacterium limosum KIST612 on different carbon and energy sources with the goal to find substrates that lead to formation of butyrate. Butyrate is an important product that can be further reduced to the highly valuable biofuel butanol in a two‐step enzymatic process.